PENTINGNYA MUSIC ART EDUCATION TERHADAP PEMBENTUKAN KARAKTER SISWA DI SD GMIT 2 KEFAMENANU, KOTA KEFAMENANU, KABUPATEN TIMOR TENGAH UTARA - Kabnani, Jefri; Lestari Salau, Triati; Iswanto; Novita Sheldena, Devi; Lakapu, Luisa (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
The purpose of this Community Service (PKM) is to be able to provide knowledge, skills and new ideas about building children's character through Art Education. Some of the activities that will be carried out are first, workshops on art education and its relation to children's character. Second, knowledge for teachers or educators of the importance of art education in elementary schools. Through music art education in elementary schools, it can increase the enthusiasm of students in learning and form good character. The method of implementing this PKM activity is the Participatory Action Research (PAR) approach where the process aims to learn in overcoming problems and fulfilling the practical needs of the community, as well as knowledge production, and the process of changing character. PKM with this approach can be said to be Transformative PKM. This is because it is a research process that is oriented towards empowerment and change. As an example of the method using the provision of music arts education materials, training and discussion.The results and outputs targeted by this service are that with Art Education training in schools, teachers and students will be motivated not to rule out Art Education as a secondary science but can be seen as an important science in the formation of children's character from an early age. This PKM activity in the form of seminars and workshops supporting art activities at SD GMIT 2 Kefamenanu was held on 30 May - 30 July 2022 with 30 participants. One way of developing this service is art education materials and the practice of music arts in the school environment whose existence can shape and improve children's character to become more skilled, innovative and creative. The PKM which was carried out at GMIT 2 Kefamenanu Elementary School, Kefamenanu City, North Central Timor Regency had a positive impact on the school, especially for educators. One of them is an initiative from educators to form art groups in schools. This is felt necessary by educators because through art groups in schools will shape the character not only for educators but also for students who study art. The art group that will be formed aims to foster a sense of liking and liking in educators and students for art. It is hoped that the art group formed can create a different atmosphere in schools such as fostering enthusiasm for educators and students in learning.